Double rare ABO blood group inheritance (KYAMC Journal, 2013)
Blood group system ABO phenotype Oh Bombay detected while cross-matching with different donors and by the by, family screening leads to a unusual matting result when mother AB and father O.DOI: http://dx.doi.org/10.3329/kyamcj.v1i2.13321KYAMC Journal Vol.1(2) January 2011, 84-86